Monitoramento do pH de dejeto bovino pré-tratado com reagentes ácido e alcalino - ANDRADE, Willian Rufino; SANTOS, Tânia Mara Baptista; SANTOS, Tânia Mara Baptista; VASO, Larissa Maria; VASO, Larissa Maria (ANAIS DO ENIC, 2017)
-